Differences between users’ and addiction medicine experts’ harm and benefit assessments of licit and illicit psychoactive drugs: Input for psychoeducation and legalization/restriction debates - Bonnet, Udo; Specka, Michael; Kanti, Ann-Kristin; Scherbaum, Norbert (Frontiers in Psychiatry, 2022)
Background There is a lack of benefit/harm assessments of illicit and licit psychoactive substances performed by substance-dependent users in comparison to addiction medicine experts. Methods We extended the analyses of substance harm/benefit assessments of German addiction medicine experts (N = 101), in parts reported recently in this journal [doi.org/10.3389/fpsyt.2020.59219], by the perspectives of substance-addicted persons. The same questionnaire as used for the abovementioned “experts-study” was handed out to inpatient detoxification or rehab treatment seeking German substance-dependent adults (N = 117) for a subsequent structured interview about harms and benefits of 33 new and traditional psychoactive substances comprising also prescription drugs. Results and discussion Both, users and experts, ranked the traditional illicit psychoactive substances heroin, cocaine and amphetamines within the top overall harm level group. Synthetic cannabinoids, alcohol and benzodiazepine were in a subordinate top-harm level position. Both cohorts also ranked methadone, nicotine and cannabis within the midrange and buprenorphine as well as psychotropic mushrooms within the lowest harm level positions. Experiences with prescription drugs (including opioidergic analgesics and gabapentinoids), cathinones, GHB, methamphetamine and methylphenidate was not prevalent in our user population. The same applied to barbiturates, propofol, kratom, ayahuasca with nearly zero assessments for each substance. The most user-experiences (>50% per assessed substance) were reported with nicotine, cannabis, alcohol, cocaine, heroin, amphetamine and methadone (core group). The user’s overall harm ratings in terms of these psychoactive substances were similar to those of the experts with the exception of the methadone assessment which was rated by the experts to be significantly less harmful if compared with the users’ estimation (supposed “treatment bias” of experts). The users’ benefit ratings for the traditional illicit psychoactive substances, cannabis as well as for nicotine were significantly more positive in comparison to those of the experts (supposed “attraction bias” of users). Both, experts and users, ranked the harms arising from the use of alcohol or benzodiazepines (usually unregulated substances) higher than the harms caused by the use of methadone, cannabis or psychotropic mushrooms (regulated by most Western narcotic acts). Users attributed the most benefits to buprenorphine, methadone and cannabis. This might reflect a main limitation of the study as the data are from an user population comprising over 50% patients who sought detoxification-treatment of opiates where methadone and buprenorphine are usual transient medications (supposed “selection bias”). Conclusion This study addressed current trends of psychoactive substance abuse (e.g., synthetic cannabinoids, prescription drugs) and provides from both perspectives (that of the user and that of the addiction medicine experts) robust harm/benefit evaluations at least of a core group of psychoactive substances (traditional illicit psychoactive substances, cannabis, methadone, alcohol and nicotine). The results of this study can be valuable to the psychoeducation of substance-addicted individuals and to current restriction/legalization debates, especially in the Western-EU.